2019
DOI: 10.2478/rjim-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three risk scores to predict outcomes in upper gastrointestinal bleeding; modifying Glasgow-Blatchford with albumin

Abstract: Introduction. Management of upper gastrointestinal bleeding (UGIB) is of great importance. In this way, we aimed to evaluate the performance of three well known scoring systems of AIMS65, Glasgow-Blatchford Score (GBS) and Full Rockall Score (FRS) in predicting adverse outcomes in patients with UGIB as well as their ability in identifying low risk patients for outpatient management. We also aimed to assess whether changing albumin cutoff in AIMS65 and addition of albumin to GBS add predictive value to these sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…Several scoring systems have been used to determine the disposition of a patient and risk for rebleeding/complication. Patients with low Blatchford scores that is 1 or less do not need to be admitted to the hospital and can be safely discharged without an inpatient endoscopy [9][10][11][12]. The management of low-risk UGIB outpatients reduces costs, as expenditure is primarily due to inpatient hospitalizations ($13,059 for the UGI-bleed cohort vs. $729 for the general population cohort) [13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Several scoring systems have been used to determine the disposition of a patient and risk for rebleeding/complication. Patients with low Blatchford scores that is 1 or less do not need to be admitted to the hospital and can be safely discharged without an inpatient endoscopy [9][10][11][12]. The management of low-risk UGIB outpatients reduces costs, as expenditure is primarily due to inpatient hospitalizations ($13,059 for the UGI-bleed cohort vs. $729 for the general population cohort) [13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of Shafaghi et al (2019) [ 18 ] was to assess the efficacy of three famous assessment methods, AIMS65, GBS, and FRS, to forecast unfavorable results in individuals with UGIB and to determine lower-risk individuals for outpatient care. They also wanted to see if adding albumin to GBS and modifying the AIMS65 albumin cutoff added prognostic validity to such ratings.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, patients with severe comorbidities might exhibit a low level of s-Alb. One study found that GBS combined with s-Alb could identify inpatient mortality in UGIB patients better than GBS and RS alone ( 33 ). Another study showed that patients who died from gastrointestinal bleeding had significantly lower s-Alb levels than those who survived ( 34 ).…”
Section: Discussionmentioning
confidence: 99%